MODELING OF THE PARAMETERS OF A FIBER-OPTIC REFRACTOMETRIC CONVERTER - Tatyana I. Murashkina; Vladislav A. Badeev; Nadezhda A. Khasanshina; Aleksandr V. Badeev; Evgeny A. Dudorov (Измерение, мониторинг, управление, контроль, 2024)
Background. Environmental protection involves the development and improvement of the design theory, technological processes and manufacturing procedures for sensors of various physical quantities, among which a significant place is occupied by sensors for the quality of liquid media, including fiber-optic sensors for the parameters of liquid media. For the express analysis of the composition of substances, a refractometric method and a fiber-optic device for its implementation have been patented. The object of research is refractometric fiber-optic measuring transducers, the main elements of fiber-optic sensors for environmental protection systems. The subject of the study is the physical, technical and geometric parameters of refractometric fiber-optic measuring transducers (FOMT). The aim of the work is to increase the sensitivity of the conversion of fiber-optic sensors for the quality of liquid media used in environmental protection systems. Materials and methods. To achieve this goal, mathematical modeling is performed to determine the physical, technical, structural and technological parameters of the micro-optical system of the FOMT. Results. The results of modeling the optical and geometric parameters of the sensor element FOMT, which is a transparent tube with a small diameter comparable to the diameter of the optical fiber used in the sensor design, are presented. The inner and outer diameters of the tube and the refractive index of the tube material are determined based on the assumed refractive index of the substance under study. Conclusions. Certain physical, technical and geometric parameters make it possible to increase the sensitivity of the FOMT transformation. The calculated parameters will be used in the design of fiber-optic refractometric sensors for environmental protection systems.